THE ROLE AND PLACE OF FUEL AND LUBRICANTS IN AVIATION - Axmadaliyev , Abror; Boboyev , Ilhom (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article examines the strategic importance of fuels and lubricants in the aviation industry and their impact on flight safety, engine efficiency, and operational reliability. The physicochemical properties of modern aviation fuels and lubricants, international quality standards, environmental requirements, and energy efficiency aspects are analyzed. Special attention is given to the prospects of alternative and synthetic fuels within the framework of sustainable aviation development.